Efektivitas Penetapan Harga Jual Produk dalam Meningkatkan Volume Penjualan Pada UMKM Pabrik Tahu Barokah - Mawar Masita Dai; Mattoasi; Siti Pratiwi Husain (SAFE-Network, 2023)
This study discusses the effectiveness of product selling price determination in increasing sales volume in Micro, Small and Medium Enterprises (UMKM) Barokah Tofu Factory in Bube Baru Village. The main objective of this study was to determine the level of effectiveness of setting the selling price on sales volume at the UMKM Barokah Tofu Factory in Bube Baru Village. The research method used is descriptive quantitative. Data is collected through observation and documentation. The results of this research show that setting effective selling prices can increase sales volume at the Barokah Tofu Factory UMKM. The analysis results show that raw material costs, labor costs and factory overhead costs play an important role in determining selling prices. In addition, the determination of gross profit must be effective so that it does not have an impact on setting selling prices that can be reached by consumers. In the context of the Barokah Tofu Factory UMKM, this research concludes that effective pricing can increase sales volume. The implications of this research provide guidance for similar UMKM in optimizing their selling price setting to achieve an increase in sales volume in achieving the organization's vision.